Well-being and environmental policy stringency (EPS) - Aw, Eugene Wei En (2018)
The economic effects of environmental policies are of paramount interest to policymakers. The traditional approach focuses on using income (Gross Domestic Product) as the leading indicator for the effects of environment policies. Higher GDP indicates that the economy is doing well but it does not fully account for an individual’s economic welfare. Happiness is not only derived from an increase in income, which is why studies that link environmental policies to happiness are of great interest. Using cross-country data, our results suggest that there is a significant relationship between EPS and a nation’s well-being, where a more stringent environmental policy leads to an improved well-being. The dominant view in current literature is that income is the most influential factor that affects happiness level. Even after controlling for GDP in our regressions, the estimates have proven that EPS is still significant in increasing a country’s happiness level. Our results lead to important policy implications, where governments around the world can increase the happiness level of their citizens by implementing stricter environmental policies.